Palliative care for children with cancer : primary caregivers perspectives - Mataga, Daphney (My University, 2018)
Palliative care plays an important role in improving quality of life for people and family members affected by life-threatening illness. The primary aims of the study were to explore the perspectives of primary caregivers on palliative care and establish the specific roles they fulfil and coping strategies they employ in palliative care of a child with cancer. The research study employed a qualitative approach which was exploratory and descriptive in nature and a case study design was used. The unit of analysis was ten primary caregivers of the children diagnosed with childhood cancer and receiving palliative care in the Pediatric Hematology and Oncology unit at Charlotte Maxeke Johannesburg Academic Hospital. Purposive sampling, a type of non-probability sampling was employed to select primary caregivers of a child with childhood cancer. A semi-structured interview schedule, with mainly open-ended questions was used, to guide the conversation and capture in depth responses from participants. Thematic analysis was employed to analyse collected data. The study revealed that caregivers are not well informed about palliative care and what it entails. The study showed that participants saw their role as giving the basic assistance such as bathing, feeding and also providing both physical and emotional support to the patient. It was evident that this gave them satisfaction as it allowed them to be involved in the care of their children. The study also noted that participants used religion as means of coping. Most participants included prayer as a source of strength and perseverance in their caregiving activities. In addition, the study also found that most participants are not aware of the professional services available for them and their children to ensure their psychological wellbeing. During palliative care of a patient diagnosed with childhood cancer it is important that professionals attend to the psychosocial wellbeing of the caregivers as it can negatively impact on the patient’s emotional wellbeing. It is thus anticipated that the findings of this study will help in assisting social workers in understanding how better to meet caregivers’ psychosocial needs. Keywords: Paediatric Palliative care, childhood cancer, primary caregivers, beliefs, coping strategies.
A report on a research study presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of requirements for the degree of Bachelor of Social Work